Lexical Strings in EFL Textbooks: SFL Analysis and Teaching Implications - Darong, Hieronimus Canggung; Susanto, Indra; Selamat, Ely Heldy Diana; Ekalia, Yulian Juita; Jelimun, Maria Olga (JOALL (Journal of Applied Linguistics and Literature), 2024)
Textbooks play a crucial role in the teaching-learning process by offering students a well-organized and thorough source of information. They function as an essential educational resource, motivating pupils to attain fluency in the desired language. This qualitative study examines the lexical string pattern of two English as a Foreign Language (EFL) textbooks using Systemic Functional Linguistics (SFL). By focusing on lexical strings, it aims to uncover how vocabulary is sequenced and contextualized within the texts, providing insights into the coherence and cohesion strategies employed. As their capacity to disclose social and cultural aspects of language use, as well as their authenticity, intertextuality, interactive quality, and communicative roles, reading passages samples from the textbooks were selected and modified into clauses for analysis. The results show repetitive, synonymous, and meronymic counts provide insights into language usage and contribute to the overall texture and structure of the analysed texts. On the other hand, higher counts of lexical strings and lexical relations suggest a higher level of diversity and complexity. The results have pedagogical implications for effective EFL teaching. In this respect, teachers can improve vocabulary retention and coherence in language instruction by using strategic approaches based on their awareness of the dominance of repetition and short lexical strings. Thus, this study gives a significant contribution to the field of EFL teaching by providing teachers to create more contextually appropriate and successful language teaching resources that will accelerate students' development of language proficiency. For students, it offers enhanced learning materials tailored to their needs, promoting faster and more effective language acquisition.